2018
DOI: 10.2116/analsci.18p367
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Paraffin-embedded Basal Cell Carcinoma Using Electron Paramagnetic Resonance

Abstract: Basal cell carcinoma (BCC) in paraffin-embedded specimens was investigated by nondestructively electron paramagnetic resonance (EPR) and X-band (9.45 GHz) EPR imaging (EPRI). A histopathological examination of specimens showed the melanin contents and revealed that they were predominantly of the nodular types. A single-line EPR pattern was observed in the BCC specimens, and the spectra of the samples were analyzed using linewidth and spectral pattern parameters. The eumelanin-related radical was observed in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Notably, a paraffin sample containing no tissue was also measured, and no signal was observed. Based on a single line, ΔHpp (0.58), g-value (2.004), and the previous data, 8,10 the radical is the eumelaninrelated radical. In addition, pigmented SK was suggested to contain melanin.…”
Section: Epr Imaging (Epri)mentioning
confidence: 89%
See 2 more Smart Citations
“…Notably, a paraffin sample containing no tissue was also measured, and no signal was observed. Based on a single line, ΔHpp (0.58), g-value (2.004), and the previous data, 8,10 the radical is the eumelaninrelated radical. In addition, pigmented SK was suggested to contain melanin.…”
Section: Epr Imaging (Epri)mentioning
confidence: 89%
“…Note that a nonpigmented tissue (control) shows no recognizable EPR signal, as we reported. 10 In addition, we measured the permeability of the paraffinembedded SK samples; the values are listed in Table 1. We found that there is a reasonable correlation between the EPR intensity and the permeability, which is directly related to the sample color tone.…”
Section: Epr Imaging (Epri)mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Melanin (eumelanin) radicals in biomedical samples have been studied using the EPR technique in various ways, such as using paraffin-embedded human MM and human and basal cell carcinoma (BCC) specimens. 8 Melanin radicals in MM and nevus pigmentosus (NP) specimens have also been compared using EPR. 5 However, melanin radicals in paraffin-embedded various specimens at ambient temperatures have not been characterized using permeability value.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, melanin (mostly eumelanin) has been extensively studied; in several studies, melanin radicals in naturally occurring melanin radicals were detected using EPR. 5,7,8 However, research on pheomelanin and its radical is limited. Pheomelanin is photosensitive and is decomposed by light, such as UV.…”
Section: Introductionmentioning
confidence: 99%